EFFECT OF SOME CLIMATIC FACTORS ON THE POPULATION DYNAMICS OF SILVERLEAF WHITEFLY BEMISIA TABACI INFESTING COTTON PLANT GOSSYPIUM HIRSUTUM (Acta Entomologica Serbica, 2019)
The present study was undertaken to examine the effect of different weather parameters on the population dynamics of silverleaf whitefly Bemisia tabaci growing on cotton (Gossypium hirsutum) plants during the years 2017 and 2018. The whitefly infestation was initially noticed on the crop at 28th and 27th meteorological standard weeks (MSW), with population densities of 0.9 and 0.35 whiteflies/3 leaves during the years 2017 and 2018, respectively. It was found that the population of the insects increased with the advancement of crop growth and reached its peak at 8.53 whiteflies/3 leaves in 35th MSW during 2017 and 12.58 whiteflies/3 leaves in 37th MSW during 2018, when the crop was in the boll-development stage. Later, the population showed a decreasing trend, reaching its minimums of 0.8 and 1.18 whiteflies/3 leaves at 50th MSW during 2017 and 2018, respectively.The above data indicate that silverleaf whitefly populations on cotton plants are favored by low temperatures and morning humidity, while rainfall did not significantly affect the dynamics: this could help in devising effective strategies against whitefly and prevent the infestation of cotton or related economically important agriculture.